Race to Witch Mountain [videorecording (DVD)] - Fickman, Andy; Johnson, Dwayne, 1972-; Robb, AnnaSophia, 1993-; Gugino, Carla, 1971-; Ludwig, Alexander, 1992-; Scott, Tom Everett, 1970-; Key, Alexander, 1904-1979 (Disney DVD., 2009)
Jack Bruno is a Las Vegas cab driver. Scientist Dr. Alex Friedman is one of his passengers. She is giving speeches about legitimate scientific theories of UFOs and outer space. The next day Jack notices Sara and Seth sitting in the back seat of his cab. He takes them to a run down house in the middle of nowhere, where they must obtain an object. Meanwhile, Major Henry Burke is searching for information pertaining to two aliens that landed days earlier. The children are captured by the U.S. government and taken to a secret facility. Now Jack and Alex must find and rescue the kids so they can continue with their mission.